Análisis de las estrategias financieras aplicables en la creación de microempresas por madres cabeza de hogar en el municipio de Saravena, (Arauca) (2022)
This project seeks to analyze the impact of financial education on the creation of microenterprises or enterprises focusing on mother’s head of household in the municipality of Saravena, in the department of Arauca. Notably in many parts of the Colombian territory the current state of the entrepreneurial ecosystem is precarious, in this territory is no exception, especially in mothers totally responsible for the economy of their home, research is done in order to create alternatives that mitigate the consequences that have been forgotten by the state, improve socio-economic conditions, promote employment for these women in vulnerable situations by expanding their knowledge with financial education. The use of tools such as surveys was proposed, where fundamental data can be obtained for this topic; to what extent it can generate effects on the living conditions of these families if the teaching of this knowledge were implemented. Access to financing, networks of contacts or mentors and the lack of preparation and knowledge on the subject in question are the fundamental pattern to undertake and these are constant difficulties faced by mother’s head of household in the municipality of Saravena. It is exposed if financial institutions and also those belonging to the state have the responsibility of imparting economic and financial knowledge, this type of financial education refers to a small segment of the population that are directly or indirectly part of the financial and educational system, concluding that this fragment of population is out of reach the aforementioned systems and are excluded, generates negative consequences on the quality of life and on the local economy.